Increasing Mathematics Learning Outcomes Through Comic Media Multiliteration - Vina, Theresia; Amelia, Winda (PT. Marosk Zada Cemerlang, 2023)
This research was prepared with the aim of improving students' understanding and learning outcomes of mathematics using a multiliteration learning model and the media used, namely comics for class VI A students of Tiranus Elementary School, East Jakarta, Academic Year 2022/2023. The learning abilities and outcomes referred to in this study, namely the ability of students to understand learning, learning activity, motivation, evaluation and student learning outcomes in the form of values that reach the KKM limit. This type of research is Classroom Action Research, where the teacher is the implementer of learning while the researcher is the observer. The design of this study used the John Elliot model. This research was carried out in the odd semester of the 2022/2023 school year, namely from August to November. The subjects of this study were students of class VI A of Tiranus Elementary School consisting of 21 learners. The object of study is the learning outcomes of mathematics subjects of learners. Data collection techniques use observation and interviews. The data are analyzed descriptively qualitatively and presented in the form of tables and graphs. The results showed an increase in student learning outcomes, namely in the first cycle by 71.4% (sufficient category), then in cycle II it increased to 81.7% (good category). This means a 10.3% increase in student learning outcomes. Thus the use of the multiliteration learning model of comic media in mathematics subjects can be said to improve the learning outcomes of students of class VI A Tiranus Elementary School.